Correlation Between Children’s Habits of Watching Advertisement on Television and Students; Speaking Arts Competency Class VIII of SMP 01 Sosopan - Khoirunnisa, Windi; Sutikno (International Journal of Educational Research Excellence (IJERE), 2025)
The problems in this research are as follows: (1) What is the speaking ability of class VIII students at SMP Negeri 01 Sosopan for the 2024-2025 academic year? (2) What is the correlation between children's habits of watching television and the speaking skills of class VIII students at SMP Negeri 01 Sosopan for the 2024-2025 academic year? The aim of this research is to analyze the correlation between children's habits of watching television and the speaking skills of class VIII students at SMP Negeri 01 Sosopan for the 2024-2025 academic year. This study used a quantitative approach. This is based on the definition of these two aspect; namely, quantitative research includes every type of research that is based on calculating percentages, averages, chi squares, and other statistical calculations. The researchers chose class VIII-2 with a total of 25 students. The research results were as folllow: (1) In this research, the data collection tool (instrument) used was a non-test, namely in the form of a questionnaire. Based on the calculation of the t-test results on the habit of watching advertisements on television, a hypothesis was obtained that stated that the results of the questionnaire on the habit of watching advertisements on television for class VIII SMP Negeri 01 Sosopan for the 2024-2025 academic year reached 70% of what was expected.  So the hypothesis states that the results of the oral test on speaking skills for class VIII SMP Negeri 01 Sosopan are at least 60% of what was expected. From the results of the product moment test for variables